3 sonates pour piano par Beethoven. Oeuvre 31 ... No. [2] - Beethoven, Ludwig van, 1770-1827 (composer):::Creator:::::::::::: (Paris; S. Richault; France, 2023)
Early edition of the Piano Sonata no. 17 in D minor, op. 31, no. 2, published in Paris by S. Richault and reissued as part of a collection.